Optimal Central Bank Lending - Andreas Schabert (Tinbergen Institute, 2010)
We analyze optimal monetary policy in a sticky pricemodel where the central bank supplies money outrightvia asset purchases and lends money temporarily againstcollateral. The terms of central bank lending affect ra-tioning of money and impact on macroeconomic aggre-gates. The central bank can set the policy rate and itsinflation target in a way that implements the first bestlong-run allocation, which is impossible if money weresupplied in a lump-sum way (as commonly assumed).Efficient central bank lending further increases gainsfrom macroeconomic stabilization beyond pure interestrate policy. This requires departing from a Treasuries-only regime.
Keywords: E4; E5; E32; 330; Optimal monetary policy; central bank instruments; collateralized lending; liquidity premium; inflation; Geldpolitik; Kreditsicherung; Liquidität; Preisrigidität; Inflationssteuerung; Theorie